2015
DOI: 10.1080/15401383.2014.935546
|View full text |Cite
|
Sign up to set email alerts
|

Foster Care Chronicles: Use of the Arts for Teens Aging Out of the Foster Care System

Abstract: This article describes the use of narrative and drama therapies as creative therapeutic interventions to engage and assist vulnerable youth. Foster Care Chronicles was a collaboration between a state university social work program and a local department of social services in a child welfare unit. This 2-year exploratory project employed an innovative approach to work with foster care youth, all of whom were within 2 years of "aging out" of care. The project utilized narrative therapy and drama therapy in a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Alguns dos programas analisados já apresentavam preocupação especial com aspectos sociais e emocionais, como por exemplo, os programas Foster Care Chronicles (Nsonwu et al, 2015), Moving On e Friendship Group (Goyette et al, 2016). Estas propostas partiram do pressuposto de que a transição para a vida adulta está infl uenciada por uma série de fatores que extrapolam a responsabilidade individual, para intervir terapeuticamente na expressão de emoções associadas à saída do acolhimento e na construção de relacionamentos saudáveis (Goyette et al, 2016).…”
Section: Discussionunclassified
“…Alguns dos programas analisados já apresentavam preocupação especial com aspectos sociais e emocionais, como por exemplo, os programas Foster Care Chronicles (Nsonwu et al, 2015), Moving On e Friendship Group (Goyette et al, 2016). Estas propostas partiram do pressuposto de que a transição para a vida adulta está infl uenciada por uma série de fatores que extrapolam a responsabilidade individual, para intervir terapeuticamente na expressão de emoções associadas à saída do acolhimento e na construção de relacionamentos saudáveis (Goyette et al, 2016).…”
Section: Discussionunclassified
“…Some of the factors identifi ed by participants as essential to ensure a healthy transition process were relationships with adult reference fi gures, support networks, socioemotional support and satisfactory relationships with educators or institutional caretakers. Some of the programs analyzed, such as the Foster Care Chronicles (Nsonwu et al, 2015), Moving On and the Friendship Group (Goyette et al, 2016), had already elected to focus on social and emotional issues. The idea that the transition to adult life is infl uenced by a series of factors beyond individual responsibility prompted these programs to focus their interventions on the expression of emotions associated with leaving foster care and the construction of healthy relationships (Goyette et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Young people and carers reported that they enjoyed their time in the theatre setting, and that they had developed social networks, relationship-based skills and confidence. Correspondingly, Nsonwu et al. (2015) explored the utility of drama as a creative therapy for young people about to transition out of the foster care system.…”
Section: Arts Interventions With Care-experienced Young Peoplementioning
confidence: 99%
“…Young people and carers reported that they enjoyed their time in the theatre setting, and that they had developed social networks, relationship-based skills and confidence. Correspondingly, Nsonwu et al (2015) explored the utility of drama as a creative therapy for young people about to transition out of the foster care system. Participants highlighted key benefits from taking part, including respect and recognition as an individual; reduced social isolation; peer bonding; and confidence in their ability to construct plans for the future.…”
Section: Introductionmentioning
confidence: 99%